PENGARUH MEDIA KARTU HURUF TERHADAP KEMAMPUAN MEMBEDAKAN HURUF DALAM MENULIS PADA PESERTA DIDIK KELAS IA UPTD SD NEGERI HOMBOL - Ade Melisa Koilhing; Yessy Mata; Halena M. Bekata (ADIBA : JOURNAL OF EDUCATION, 2026)
This study aims to determine the effect of letter cards on the ability to distinguish letters in writing among grade IA students at the Hombol Public Elementary School Technical Implementation Unit (UPTD SD Negeri Hombol). The quantitative research method used in this study was a pre-experimental study with a one-group pre-test and post-test. The independent variable in this study was the letter cards, and the dependent variable was the ability to distinguish letters in writing. The population in this study was all students at the UPTD SD Negeri Hombol, with a sample size of 20 students in grade IA. The researchers collected data using prerequisite test data collection techniques (normality test) and statistical tests (simple linear regression and t-test). The results showed an increase in the average score from 43.80 (poor category) in the pretest to 72.20 (sufficient category) in the posttest. The results of the simple linear regression test showed a positive regression coefficient with a significance value of 0.084 <0.05, indicating that the letter cards significantly influenced the ability to distinguish letters in writing. The conclusion of this study is that the use of letter cards effectively improves the ability to distinguish letters in writing for class IA students at the Hombol State Elementary School UPTD. Based on the data above, the researcher concludes that H_0 is rejected and H_1 is accepted, which means that the effect of letter cards on the ability to distinguish letters in writing for class IA students at the Hombol State Elementary School UPTD.